Pengaruh Harga dan Kualitas Produk terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan sebagai Variabel Intervening - Asma'ul Khusna, Elda Fitra; Nirawati, Lia (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the effect of price and product quality on customer loyalty through customer satisfaction as an intervening variable on @vivo_indonesia Instagram followers. This type of research is quantitative research, while in this study, the population used is the @vivo_indonesia Instagram account which has 857,171 followers, with the sampling technique using purposive sampling. Data was collected through a questionnaire with descriptive and inferential statistical analysis techniques using the Smart-PLS 4.0 program. Based on the results of this study, it is concluded that price has a positive and significant effect on customer satisfaction. Product quality has a positive and significant effect on customer satisfaction. Customer satisfaction has a positive and significant effect on customer loyalty. Price has a positive and insignificant effect on customer loyalty. Product quality has a positive and significant effect on customer loyalty. Price has a negative and significant effect on customer loyalty through customer satisfaction. Product quality positively and significantly affects customer loyalty through customer satisfaction. Keywords: Price, Product Quality, Customer Satisfaction, Customer Loyalty